Discrete Energies of a Weakly Outcoupled Atom Laser Beam Outside the Bose–Einstein Condensate Region - Prayitno, Teguh Budi (UI Scholars Hub, 2014)
We consider the possibility of a discrete set of energies of a weakly outcoupled atom laser beam to the homogeneous Schrödinger equation with anisotropic harmonic trap in Cartesian coordinates outside the Bose–Einstein condensate region. This treatment is used because working in the cylindrical coordinates is not really possible, even though we implement the cigar-shaped trap case. The Schrödinger equation appears to replace a set of two-coupled Gross– Pitaevskii equations by enabling the weak-coupling assumption. This atom laser can be produced in a simple way that only involves extracting the atoms in a condensate from by using the radio frequency field. We initially present the relation between condensates as sources and atom laser as an output by exploring the previous work of Riou et al. in the case of theoretical work for the propagation of atom laser beams. We also show that even though the discrete energies are obtained by means of an approaching harmonic oscillator, degeneracy is only available in two states because of the anisotropic external potential